Selection of the Better Dual-Timed Up and Go Cognitive Task to Be Used in Patients With Stroke Characterized by Subtraction Operation Difficulties - Pumpho, Ampha; Chaikeeree, Nithinun; Saengsirisuwan, Vitoon; Boonsinsukh, Rumpa (Frontiers in Neurology, 2020)
Background: The Timed Up and Go Test (TUG) with serial subtraction is commonly used to assess cognitive dual-task performance during walking for fall prediction. Some stroke patients cannot perform number subtraction and it is unclear which cognitive task can be used to substitute for the subtraction task in the TUG test. The aim of this study was to determine the type of cognitive task that produced the highest decrease on both motor and cognitive performances during TUG-dual in stroke patients. Methods: 23 persons with stroke capable of completing subtraction (ST) and 19 persons with subtraction operation difficulties (SOD) participated. Both groups have a similar age range (ST: 59.3+10.4 years and SOD: 62.0+6.8 years) and stroke onset duration (ST: 44.13+ 62.29 months and SOD: 42.34+39.69 months). Participants performed TUG without a cognitive task (TUG-single) followed by a cognitive task when seated (cognitive-single). In addition, TUG with a cognitive task (TUG-dual) was performed, with the activity randomly selected from 4 cognitive tasks, including alternate reciting, auditory working memory, clock task, and phonologic fluency. Main outcome variables; TUG duration measured by OPAL accelerometer and cognitive dual-task effect (DTE) were analyzed using repeated-measures ANOVA. Results: Number of correct responses when seated were significant lower in the SOD as compared to the ST (p < 0.05) during all cognitive tasks, except the phonologic fluency. During TUG-cognitive, TUG duration in the ST was significantly longer for all cognitive tasks compared with TUG-single (p < 0.0001), whereas TUG duration in the SOD was significantly increased only during the phonologic fluency task (p < 0.01). In the ST, there was a significant difference in cognitive DTE between the subtraction and phonologic fluency task (p < 0.01). The highest cognitive cost was found in the subtraction task whereas the highest cognitive benefit was shown in phonologic fluency task. No significant cognitive DTE was found among cognitive tasks in the SOD. Conclusion: For stroke persons with subtraction operation difficulties, phonologic fluency is suitable to be used in the TUG-cognitive assessment. In contrast, subtraction (by 3) is recommended for the assessment of TUG-cognitive in stroke persons who can perform subtraction.